PENGEMBANGAN MEDIA REALIA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Kuswariyanti, Ninik (Universitas Insan Budi Utomo, 2021)
Realia media is a real object that can be used as a tool in learning activities. The realia media used are free, can be in the form of straws, beads, legos, or whatever objects are owned by students to support learning activities. The purpose of this study was to improve student learning outcomes in mathematics in the distribution material. The research method used was Classroom Action Research in grade 2 SD Negeri Kedungcaluk 1, Krejengan District, Probolinggo Regency in the even semester of the 2019/2020 school year. The results showed that the test scores of student learning outcomes from pre-cycle to cycle 1 then cycle 2 increased significantly, namely 11.68% from the average test value in pre-cycle to cycle 1, then there was an increase of 6.44% from the cycle. 1 to cycle 2. In addition to improving learning outcomes, media realia also fosters enthusiasm and motivation for student learning and trains students to reason well independently in finding their own traditional division algorithms.